Mixed Methods in VET Research: Usage and Quality - Cameron, Roslyn (Australian Vocational Education and Training Research Association, 2010)
Mixed methods had been heralded as the third methodological movement with several authoritiesfrom across an array of discipline fields contributing to a growing body of literature and theoreticaldevelopments. The discipline fields which are showing high levels of acceptance for mixed methodsare those related to education, health and nursing, social and behavioural sciences and business/management disciplines. This third methodological movement is now beginning to address issues of quality in the reporting of mixed methods studies. The movement is beginning to question whether researchers utilising mixed methods have gone beyond the one dimensional and relatively rudimentary concept of triangulation to embrace the more complex designs and methodological theory being developed. The aim of the study is to explore the use and quality of mixed methods in vocational education research through a systematic review of a specific sample of vocational education and training(VET) based research. The paper concludes with a call for mixed methods in higher degree researchtraining curricula and a need for established VET researchers to engage with the mixed methodsfoundational literature and the new and more complex theoretical developments that are emerging.